Opioid and α2 adrenergic mechanisms are activated by GABA agonists in the lateral parabrachial nucleus to induce sodium intake - De Oliveira, Lisandra B. [UNESP] (2018)
The activation of GABA, opioid or α2 adrenergic mechanisms in the lateral parabrachial nucleus (LPBN) facilitates hypertonic NaCl intake in rats. In the present study, we combined opioid or α2 adrenergic antagonists with GABA agonists into the LPBN in order to investigate if NaCl intake caused by GABAergic activation in normohydrated rats depends on opioid or α2-adrenergic mechanisms in this area. Male Holtzman rats with stainless steel cannulas implanted bilaterally in the LPBN were used. Bilateral injections of muscimol or baclofen (GABAA and GABAB agonists, respectively, 0.5 nmol/0.2 μl) into the LPBN induced strong ingestion of 0.3 M NaCl (45.8 ± 7.3 and 21.8 ± 4.8 ml/240 min, respectively) and water intake (22.7 ± 3.4 and 6.6 ± 2.5 ml/240 min, respectively). Naloxone (opioid antagonist, 150 nmol/0.2 μl) into the LPBN abolished 0.3 M NaCl and water intake to muscimol (2.0 ± 0.6 and 0.9 ± 0.2 ml/240 min, respectively) or baclofen (2.3 ± 1.1 and 0.8 ± 0.4 ml/240 min, respectively). RX 821002 (α2 adrenoceptor antagonist, 10 nmol/0.2 μl) into the LPBN reduced 0.3 M NaCl intake induced by the injections of muscimol or baclofen (26.6 ± 8.0 and 10.1 ± 4.9 ml/240 min, respectively). RX 821002 reduced water intake induced by muscimol (7.7 ± 2.9 ml/240 min), not by baclofen. The results suggest that sodium intake caused by gabaergic activation in the LPBN in normohydrated rats is totally dependent on the activation of opioid mechanisms and partially dependent on the activation of α2 adrenergic mechanisms in the LPBN.